Obesity as a Potential Risk Factor for Vincristine-induced Peripheral Neuropathy. Issue 7 (October 2020) - Sajdyk, Tammy J.; Boyle, Frances A.; Foran, Kaitlin S.; Tong, Yan; Pandya, Pankita; Smith, Ellen M.L.; Ho, Richard H.; Wells, Elizabeth; Renbarger, Jamie L.
Abstract : Acute lymphoblastic leukemia (ALL) is the most common pediatric cancer. Vincristine is a core chemotherapeutic agent for patients with ALL; unfortunately, ∼78% will develop vincristine-induced peripheral neuropathy (VIPN). VIPN can result in vincristine dose reductions that decrease therapeutic efficacy: making it important to understand which children are at highest risk for VIPN. We hypothesized that pediatric ALL patients who were obese at diagnosis would develop worse VIPN than healthy weight children with ALL within the first year. Our results confirmed that obese pediatric patients have significantly ( P =0.03) worse VIPN than patients of healthy weight.